Charge The Immune System With Cashew Apple(Anacardiumoccidentale L.) -Torrent In Vitamin C And Iron – A Review - ameena Beebi B ,balasasirekha R (International Journal of Modern Agriculture, 2021)
The cashew apple is a tropical natural fruit and is a significant byproduct of the cashew nut handling industry. It is plentiful in vitamins, polyphenols, sugars, minerals, amino acids, and dietary fiber and can be considered as a practical food.It is usually used in the fortification of the nutritional quality of some tropical foods, because of its high percentage of vitamin C, which is a fundamental supplement to redox capacity under ordinary physiologic conditions. The principal physiological capacity of this nutrient is identified with its ability to act as a cofactor for a substantial group of compounds. Ascorbate acts to invigorate transferrin-subordinated iron uptake by an intracellular reductive mechanism, strongly suggesting that it may act to stimulate iron mobilization from the endosome. The capacity of ascorbate to direct moving iron take-up could help clarify the metabolic imperfection that contributes to ascorbate-insufficiency initiated anemia. This paper presents a jointreview of the cashew apple, the function of vitamin C in iron absorption, and treating iron deficiencyanaemia through combinational treatment